Imaging features of rhinosporidiosis on contrast CT - Prabhu, Shailesh M; Irodi, Aparna; Khiangte, Hannah L; Rupa, V; Naina, P (Indian Journal of Radiology and Imaging, 2013)
Context: Rhinosporidiosis is a chronic granulomatous disease endemic in certain regions of India. Computed tomography (CT) imaging appearances of rhinosporidiosis have not been previously described in the literature. Aims: To study imaging features in rhinosporidiosis with contrast-enhanced CT and elucidate its role in the evaluation of this disease. Materials and Methods: Sixteen patients with pathologically proven rhinosporidiosis were included in the study. Contrast-enhanced CT images were analyzed retrospectively and imaging findings were correlated with surgical and histopathologic findings. Results: A total of 29 lesions were found and evaluated. On contrast-enhanced CT, rhinosporidiosis was seen as moderately enhancing lobulated or irregular soft tissue mass lesions in the nasal cavity (n = 13), lesions arising in nasal cavity and extending through choana into nasopharynx (n = 5), pedunculated polypoidal lesions arising from the nasopharyngeal wall (n = 5), oropharyngeal wall (n = 2), larynx (n = 1), bronchus (n = 1), skin and subcutaneous tissue (n = 2). The inferior nasal cavity comprising nasal floor, inferior turbinate, and inferior meatus was the most common site of involvement (n = 13). Surrounding bone involvement was seen in the form of rarefaction (n = 6), partial (n = 3) or complete erosion (n = 3) of inferior turbinate, thinning of medial maxillary wall (n = 2), and septal erosion (n = 2). Nasolacrimal duct involvement was seen in four cases. Conclusions: Contrast-enhanced CT has an important role in delineating the site and extent of the disease, as well as the involvement of surrounding bone, nasolacrimal duct and tracheobronchial tree. This provides a useful roadmap prior to surgery.
Keywords: Bronchus; CT; disseminated; nasolacrimal duct; rhinosporidiosis